Islamic personal branding strategies in the 2024 local election in Central Aceh - Ali Mustafa (Jurnal Studi Komunikasi, 2024)
This study investigates the application of Islamic personal branding tactics by politicians competing in the 2024 Central Aceh local elections. This research, rooted in the theoretical framework of personal branding and political communication, examines how politicians in this primarily Muslim region leverage diverse media channels to shape their public image and engage the local population. The study employs a qualitative technique, including text analysis, observations, and document inspection, to evaluate the personal branding tactics of a sample of ten politicians across various media platforms that include the internet, social media, and print media. The data collection period spans six months before the 2024 Central Aceh local election. The findings show that politicians make substantial use of Islamic rhetoric, symbolism, and the involvement of religious authority to boost their personal brands. They use a consistent media strategy, carefully incorporating these Islamic personal branding elements across several interconnected mediums. Nonetheless, the study emphasises the difficulties of guaranteeing consistency between the leaders' crafted image and their actual behaviour and policies. This study enhances the limited academic understanding of the influence of religion on personal branding and political communication, specifically regarding local elections in predominantly Muslim areas. The insights acquired can guide the formulation of more effective and ethical personal branding strategies for politicians aiming to engage with their people.